DECOLONIZATION OF ISLAMIC FAMILY LAW IN INDONESIA: TRACING TRANSFORMATION AND CONTINUTIY - Mukhammad Nur Hadi; Moh. Wahib; Moh. Irfan; Abdul Kadir Riyadi (Universitas Nurul Jadid, 2026)
This article aims to explore the process of decolonization of Islamic family law in Indonesia by tracing its historical transformation, policy changes, and the continuity of its legal practices from the colonial period to the post-reform era. Through a conceptual, historical, and legislative approach, this article analyzes how the colonization of Islamic family law took place in Indonesia. This article argues that the decolonization of Islamic family law in Indonesia did not occur in a single manner, but instead in two primary forms. First, accommodative decolonization, which was realized through post-independence state policies, such as the theories of receptie exit and receptio a contrario, the Religious Court Law, the Compilation of Islamic Law, and various policies of the Supreme Court and the Ministry of Religious Affairs, which negotiated fiqh traditions with the need for modern legal protection, especially for women and children. This pattern aligns with Khaled Abou El Fadl's view, which regards legal reform as an inherent part of the Islamic legal tradition. Second, conservative decolonization is reflected in fatwas and classical fiqh discourse developed by Islamic boarding schools and religious organizations, in line with Wael B. Hallaq's criticism of colonial legal modernity. This article argues that the decolonization of Islamic family law in Indonesia is an ongoing process involving the state and religious scholars, and that it does not merely aim to erase the colonial legacy but also to create a contextual, just, and responsive Islamic family law system for vulnerable groups.